What's new in the management of proximal femoral fractures? - Nikolaou, V S; Papathanasopoulos, A; Giannoudis, P V (Injury, 2008)
The incidence of proximal femoral fractures has increased significantly in recent years, and is expected to continue to rise with increasing life expectancy. However, the optimal method of treatment of these fractures is still debated. This article summarises current evidence concerning the most controversial issues in the treatment of intracapsular and extracapsular proximal femoral fractures. Despite initial enthusiasm, many new treatment options have been proved inferior to older, traditional methods, and physicians should be cautious when it comes to managing these fractures. It seems that meticulous surgical technique and implant selection according to fracture pattern and the characteristics of the individual patient offer the best route to optimal final outcome.
Keywords: Arthroplasty, Replacement, Hip; Female; Femoral Fractures; Fracture Fixation; Humans; Life Expectancy; Male; Quality of Life; Treatment Outcome